2018
DOI: 10.1086/697542
|View full text |Cite
|
Sign up to set email alerts
|

Environmental DNA reveals nonmigratory individuals of Palaemon paucidens overwintering in Lake Biwa shallow waters

Abstract: In Lake Biwa, the largest freshwater lake in Japan, the lacustrine shrimp Palaemon paucidens has been reported to undertake seasonal migrations, living in deep waters from autumn to winter and in shallow waters from spring to summer. Some investigators have suggested that some individuals overwinter in shallow waters, but the ecology and life history of such nonmigratory populations are poorly understood. We developed a species-specific environmental DNA (eDNA) marker to detect P. paucidens in water samples an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 33 publications
2
22
1
Order By: Relevance
“…Wu et al (2019) found that relatively large individuals started to reproduce between May and July, with a peak detected between August and September. While it has been reported that most individuals move to bottom sites in winter (Harada, 1966;Nishino, 1983), we found that nonmigratory individuals overwinter in shallow waters (Wu et al, 2018).…”
Section: Introductioncontrasting
confidence: 66%
See 4 more Smart Citations
“…Wu et al (2019) found that relatively large individuals started to reproduce between May and July, with a peak detected between August and September. While it has been reported that most individuals move to bottom sites in winter (Harada, 1966;Nishino, 1983), we found that nonmigratory individuals overwinter in shallow waters (Wu et al, 2018).…”
Section: Introductioncontrasting
confidence: 66%
“…Wu et al (2018) identified a positive correlation between eDNA concentrations and the abundance of shrimps, and we assume this correlation to hold for our research. We tracked distribution of P. paucidens eDNA in Lake Biwa and found that it was determined by season and site.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations